2001
DOI: 10.1177/00912700122009953
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Modeling of Pantoprazole's Irreversible Effect on Gastric Acid Secretion in Humans and Rats

Abstract: The relationship between the pharmacokinetics of pantoprazole, an irreversible proton pump inhibitor, and its effect on gastric acid secretion was evaluated in humans and rats. Pantoprazole pharmacokinetics were studied in 6 rats (5 mg/kg, i.v.) and 22 healthy volunteers (10 to 80 mg, i.v. and oral). Gastric acid secretion under maximum pentagastrin stimulation was measured after i.v. administration of placebo or pantoprazole in 31 rats (0.12 to 1.15 mg/kg) for 4 hours and in 31 subjects (20 to 120 mg) for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
2
19
0
1
Order By: Relevance
“…In other experiments, the halftime of restoration of acid secretion in omeprazole-treated rats was 20 h [19,70]. An analysis of the rate of restoration of acid secretion in man after omeprazole inhibition suggested that the halftime was 24 h, whereas after pantoprazole, it was 46 h [12]. Apparently, only the latter drug gave a rate of recovery compatible with restoration of acid secretion as due entirely to pump turnover [9,23].…”
Section: Biology Of Proton Pump Inhibitorsmentioning
confidence: 95%
“…In other experiments, the halftime of restoration of acid secretion in omeprazole-treated rats was 20 h [19,70]. An analysis of the rate of restoration of acid secretion in man after omeprazole inhibition suggested that the halftime was 24 h, whereas after pantoprazole, it was 46 h [12]. Apparently, only the latter drug gave a rate of recovery compatible with restoration of acid secretion as due entirely to pump turnover [9,23].…”
Section: Biology Of Proton Pump Inhibitorsmentioning
confidence: 95%
“…The center diagram shows a basic model with zero-order production ( k in ), first-order loss ( k out ), and an irreversible (second-order, k·C p ) inactivation of the response parameter. This type of model has been used to account for the anti-platelet inactivation of COX-1 by aspirin (32) as well as the effects of pantoprazole and other proton pump inhibitors causing reduction in gastric acidity (33). …”
Section: Diversity Of Basic Turnover Modelsmentioning
confidence: 99%
“…The study group received subcutaneous pantoprazole (Wyeth Pharmaceuticals Inc., Philadelphia, PA) at a dose of 5 mg/kg injected subcutaneously under the neck fur every 8 h for 3 days and 1 h before the procedure. Standard PPI doses for rats vary in the literature between 5 to 20 mg/kg [4,5]. The current dose was chosen to obtain noticeable change in gastric pH in this rat model.…”
Section: Protocolmentioning
confidence: 99%